Ėrdmijn bütėėlijn ėmhėtgėl = Collection of scientific works = Sbornik naučnych trudov - Bira, Shagdaryn 1927-2022 ("Soëmbo Printing" HHK, 2018)
Collection of research works written by Sh.Natsagdorj (1918-2000), a famous historian, Academician, Long-time Vice President, Mongolian Academy of Science and Director, Institute of History, Mongolian Academy of Sciences